Rheological Properties of Guar Gum for Potential Use in Enhanced Oil Recovery in Sudanese Oil Fields - B. Nimir, Hassan; Abdel Aziz, Kamal; A. Kasha, Ahmed (University of Khartoum Engineering Journal, 2022)
Recovery from depleting Sudanese oil fields using Enhanced Recovery methods needs to be studied. Improved/Enhanced recovery techniques represent a potential to recover some of the oil left in place. One of these technologies is polymer flooding to increase the viscosity of the displacing water when compared to the viscosity of the displaced oil and consequently improve the displacement efficiency. This paper investigates different parameters that affect guar gum for potential use in Enhanced Oil Recovery Processes. Guar gum is as an abundant and environmentally safe material which can be utilized for increasing viscosity of injected water to improve the recovery of crude oil in certain oil fields. Rheological study was performed in the Petroleum Engineering laboratory for indigenous guar gum. Effects of concentration, salinity, thermal and biological degradation factors were thoroughly studied. For four different salinity waters, the viscosity of polymer in different salinity levels (encountered in field) was found to increase gradually in direct proportion with concentration and decreases with salinity. The critical micelle concentration, CMC (the concentration beyond which no remarkable change in viscosity is likely) of guar gum was found to be 0.6%. Bacterial growth is found to affect guar gum viscosity drastically. However, the effect of mechanical (shear) degradation as well as thermal degradation (temperatures up to 100 deg C) was found to be minimal. Based on these results, guar gum can be a good candidate for use in Sudanese oil fields, however further coreflood is required to quantify its performance.